Student Sex Work in the Netherlands: Motivations and Experiences - MARIA STEMPVOORT (2024)
Higher education students in the Netherlands undertake various roles in the sex industry. Insight is currently lacking into why students make the choice to work in this sector and what their experiences might be. This qualitative study seeks to address this gap. Semi-structured interviews were undertaken with 19 student sex workers and 3 students who have considered working in the sex industry. The male, female and transgender student sex workers who took part were predominantly white and were from a range of socioeconomic backgrounds. The students worked in direct and indirect forms of sex work. As an alternative to a full participatory study, the study included ‘participatory elements’ where three (student) sex workers provided feedback on the interview schedule and the recruitment material. In the Netherlands, where tuition fees for Dutch and EU students are moderate, student sex work cannot solely be explained through the lens of financial hardship. Most of the student sex workers in this study also have practical and intrinsic motivations for working in the sex industry. The flexible nature of sex work enables students to organise their work around their studies. The students derive pleasure from being with clients and enjoy connecting with them. Meanwhile, feminist-oriented students gain pleasure from their ability to put into practice their feminist beliefs in their work.That the experiences of the student sex workers in this study are pleasant overall should be seen in the light of their intersectional privilege in terms of race, class and education, their ability to access alternative recourses beyond sex work, and their access to legal occupations in the middle and higher echelons of the sex industry where, on the whole, they face relatively good labour conditions. The strata in which most students work have an elevated status and a portion of the students use this favourable position to manage the stigma of sex work and by so doing, perpetuate the stigma of sex work. The fact that the student sex workers in this study make well-considered decisions to take advantageof what the sex industry has to offer challenges the framing of sex workers as victims, which has gained currency in the Netherlands over the last few decades.